Inspiration - Banning, William Burgess (My University, 1904)
Introduction: Inspiration, - literally a breathing of new thought and life into a human being, - is as old as the human race. And what a fascinating subject for most people! Speak of it and instantly one’s thoughts turn to supernatural agencies, to visions of angels, to the insistent power of the still small voice and to times in his own life when his heart was strongly warmed and his mind on fire with an almost irresistible impulse to action, induced by a clear intellectual light that comes almost inexplicably from, - no one knows where. Theologically, Inspiration means a divine influence working in man's soul by which he is qualified to receive and teach divine moral and religious truth with authority. Ordinarily, and in the profane sense, the word means the act of exercising an elevating, stimulating, influence on the intellect and emotions of man. The physiological meaning we shall not consider.
Citation: Banning, William Burgess. Inspiration. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Inspiration; Historical Figures; Diction; Definitions; Influences; Theses